Cathodic stripping voltammetric determination of β-cyfluthrin, a pyrethroid insecticide, using polished silver solid amalgam electrode - Silva, Caio César Gonçalves [UNESP]; Silva, Lucas Moreira [UNESP]; e Silva, Beatriz Costa [UNESP]; Garrido, Saulo Santesso [UNESP]; Boldrin, Maria Valnice [UNESP]; De Souza, Djenaine (Springer Nature, 2020)
This work describes an electroanalytical procedure for determination of beta-cyfluthrin (βCF), a pyrethroid insecticide, using polished silver solid amalgam electrode (p-AgSAE) allied to a square-wave cathodic adsorptive stripping voltammetry (SWCASV). Although βCF is non-electroactive in the conventional electrodes, it was accumulated at the p-AgSAE surface as adsorbed mercury salt, allowing their indirect determination using the well-defined reduction peak of mercury complex at − 0.94 V, obtained after adequate experimental and voltammetric optimization. Analytical curves were constructed for βCF, and all analytical parameters were properly evaluated. The proposed methodology was applied in the βCF determination in natural water and tea samples, which were previously filtrated before voltammetric analysis, already the same analysis performed using gas chromatography with mass spectroscopy detection technique employed the solid-phase extraction step. Analytical parameters obtained using both techniques indicated no significant difference at 95% confidence, confirming that the electroanalytical procedure had high robustness, good stability and suitable sensitivity to determination of βCF in complex samples. [Figure not available: see fulltext.].
Keywords: Beta-Cyfluthrin; Cathodic stripping voltammetry; Electroanalytical determination; Polished silver solid amalgam electrode; Pyrethroids insecticide; Tea samples